METHOD FOR BUILDING A WORKING GEODETIC NETWORK OF REFLECTIVE MARKS FOR CONSTRUCTION NEEDS: METHOD FOR BUILDING A WORKING GEODETIC NETWORK OF REFLECTIVE MARKS FOR CONSTRUCTION NEEDS - Spasov , Petyo (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The work in the implementation of construction works for large production buildings, residential complexes, airports, sports complexes, examination of deformations and many other activities that require precise geodetic measurements can be optimized during and quality through the creation and use of geodetic reflective marks. The article discusses how to stabilize and measure the working base and part of the processing theory.